Relational permanence and the potential for delinquency among African American adolescents in foster care. (September 2020) - Williams-Butler, Abigail; Duron, Jacquelynn F.; Costantino, Amanda; Schmidt, Adam
Highlights: An increase in relational permanence is correlated with later delinquency. Findings show not all social relationships are correlated with positive outcomes. Age, gender, and time in care were also significantly related to later delinquency. Abstract: S ocial relationships are often seen as a buffer to delinquency. However, they may be correlated with negative outcomes, as delinquency may provide social benefits for adolescents in foster care. Relational permanence – a form of social support characterized by the presence of an ongoing caring and supportive person in the context of the foster care system – is the primary type of social relationship that is explored. Regression analyses were conducted examining whether relational permanence predicted later delinquency. We found an increase in relational permanence over time was correlated with higher levels of delinquency. These findings demonstrate that not all social relationships are correlated with positive outcomes. The multidimensionality of social relationships must be further understood in order to inform targeted interventions for youth in the foster care system. Considerations specifically for African-American adolescents in foster care are also addressed.